An Understanding of Character from Holistic Thinking: What Asian Psychology Teaches Us about the Debate on Situationism - Cleofas, Jacklyn A (Archīum Ateneo, 2019)
The situationist challenge to virtue has convinced many philosophers to adopt an empirically grounded methodology. I argue that this methodology requires us to reconsider conceptualizations of and evidence on character from experiments involving Asian subjects because it is precisely in these experiments that we see a remedy for the problems exposed by situationism. Since both situationists and defenders of virtue fall short of abiding by the part of their methodological commitment associated with remediation, evidence from the experiments is relevant for most participants in the debate. I show that the evidence indicates something important about remediation: the point is not to avoid the concept of virtue or character, but to deploy a holistic thinking style that has been observed among some populations in Asia. Holistic thinking involves (a) a tendency to explain behavior in terms of the interaction between person and situation variables and (b) an incremental understanding of character. The paper ends with a brief sketch of an account of character from holistic thinking that also highlights the role of social support in managing situations.